Medical Perioperative Management In Patient with Acute Kidney Disease - Caesar Ayudi; Nunuk Mardiana (Universitas Airlangga, 2020)
Bartter syndrome is inherited tubulopathy caused by mutations in several genes causing hypokalemia, hypomagnesemia, hypocalcemia with hypercalciuria, and metabolic alkalosis. Beside from inherited disorder, Bartter syndrome can be caused by the use of aminoglycosides, so it is called Bartter-like syndrome. Hypokalemia has been reported as a side effect of aminoglycosides in many studies, but Bartter-like syndrome due to aminoglycosides has only been reported in a few case reports. We report a 43 years old female patient who developed muscle weakness due to hypokalemia. We found the patient’s laboratory results was consistent with Bartter syndrome. The patient had MDR-TB and received combination therapy with capreomycin for two months. We diagnosed a patient with Bartter-like syndrome due to capreomycin. Following diagnosis, we discontinued capreomycin and started potassium, magnesium and calcium therapy. After electrolyte imbalances improved, capreomycin was given three times per week and the patient was no longer experiencing the same condition.